MASTERPIECE OF ABUYAHYA IMODUDDIN ZAKARIAI QAZVINI («MODERN PHILOLOGICAL PARADIGMS: INTERACTION OF TRADITIONS AND INNOVATIONS», 2025)
The article is devoted to the recognition of masterpiece of Abuyahya Imoduddin Zakariai Qazvini «Āthār al-bilād wa-akhbār al-ʿibād» by Zakariya Qazwini, in which the author tried to present the mentioned book to the reader in an understandable and scientific language based on sources, research works and manuscripts within one article. The article discusses geographical science, world geographers, previous research on the theme being studied, the importance of studying «Āthār al-bilād wa-akhbār al-ʿibād», its manuscripts, publications and translations.
Keywords: Geography, Zakariya Qazwini, «Āthār al-bilād wa-akhbār al-ʿibād», translation and publication of the work.